Evaluating sexual nursing care intervention for reducing sexual dysfunction in Indonesian cervical cancer survivors - Yati Afiyanti; Imami Nur Rachmawati; Ariesta Milanti (Asia-Pacific Journal of Oncology Nursing, 2016)
Objective: This study aims to describe the factors affecting successful nursing care intervention on sexuality. Methods: A one-group pre- and post-test design was used. Fifty-three cervical cancer survivors and their spouses were administered with nursing care intervention on sexuality in three sessions and evaluated after 6 weeks. Results: Sexual intervention reduced dyspareunia symptoms, improved vaginal lubrication, improved sexual satisfaction, and enhanced sexual arousal, sexual desire, and orgasm among cancer survivors and their spouses. The other influencing factors also simultaneously contributed to the success of nursing care intervention. Conclusions: Nursing care intervention on sexuality could be a part of supportive nursing care and an important aspect in standard nursing care for cancer patients in Indonesia.